DISKURSUS GENDER DALAM PENDIDIKAN ISLAM - Iqbal, Mahathir Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2015)
Our religious orientation today is still dominated by the bias of the normative discourse of women’s interests. Especially regarding gender relations. We actually realize that many religious law, personal law such families, religious practices, and including also the social and political leadership over the legitimacy of religious especially for women, is based on the assumption of patriarchy and sexism. The system is based on patriarchy and sexism, usually alienate women at home, so men are more able to dominate women. Gender discourse in Islamic education clearly has a very important relevance. In fact, the discourse of gender and sexism can be on the agenda the study of new forms of equality and egalitarianism represents justice discourse. This gender studies, for example, can be used as an alternative paradigm construction amid strong conservative currents would strive to restore the role of women to the domestic sector, with a variety of pragmatic legitimacy, religious, or ideological science. One of the immediate urgent effort is how to formulate a concept of gender oriented Islamic education